Natural Variation in Crops: Realized Understanding, Continuing Promise - Liang, Yameng; Liu, Hai-Jun; Yan, Jianbing; Tian, Feng (Annual review of plant biology, 2021)
Crops feed the world's population and shape human civilization. The improvement of crop productivity has been ongoing for almost 10,000 years and has evolved from an experience-based to a knowledge-driven practice over the past three decades. Natural alleles and their reshuffling are long-standing genetic changes that affect how crops respond to various environmental conditions and agricultural practices. Decoding the genetic basis of natural variation is central to understanding crop evolution and, in turn, improving crop breeding. Here, we review current advances in the approaches used to map the causal alleles of natural variation, provide refined insights into the genetics and evolution of natural variation, and outline how this knowledge promises to drive the development of sustainable agriculture under the dome of emerging technologies. Expected final online publication date for the , Volume 72 is May 2021. Please see http://www.annualreviews.org/page/journal/pubdates for revised estimates.